Is Walking Necessary for Effective Locomotion and Interaction in VR? - Hashemian, Abraham M.; Adhikari, Ashu; Bretin, Alexander; Aguilar, Ivan; Kruijff, Ernst; Heyde, Markus von der; Riecke, Bernhard E. (IEEE VR Workshop on Finding a way forward in VR locomotion, 2021)
his paper reports on a work-in-progress study to investigate if/how leaning-based interfaces affect simultaneous locomotion and interaction. We compare physical walking and Controller with a seated (i.e., HeadJoystick) and standing (i.e., Naviboard) leaning-based interface. We disambiguated performance in locomotion versus interaction using a novel experimental paradigm, where participants should point toward moving targets using their virtual light-saber while actively following a moving platform.
Keywords: 2-page conference paper; NSERC DG 2026; Riecke; Riecke_2021; abraham-hashemian; ashu-adhikari; bernhard-riecke; conferencePaper; conferencePapers; ernst-kruijff; extended-abstract; ivan-aguilar; markus-von-der-heyde; motion-cueing; proj--LightSaber; proj--locomotionAndInteraction; proj--motionCueingInterfaces; proj--naviboard; short conference paper